Evaluation of the consumption of slimming drugs dispensed in a drugstore (Research, Society and Development, 2020)
Obesity is classified as a public health problem affecting millions of people worldwide. Therefore, anorexigenic drugs are seen as allies to fight the disease, however, abusive and irrational consumption can generate health risks. Thus, the objective was to investigate the outputs of the main weight loss dispensers, addressing the risks that this medication can cause. This study is a quantitative, descriptive, retrospective research model carried out from September to October 2019 in a drugstore located in Teresina Piauí. Regarding the dispensation of the main weight loss products from January 2017 to December 2018, the results point sibutramine as the only psychotropic anorexigen dispensed, obtaining a reduction of 7% in the years evaluated, demonstrating greater control in the sale. On the other hand, there was an increase in the weight loss marketed without restriction of medical prescription. There is then a reduction in the consumption of sibutramine in the drugstore, reflecting the control that RDC No. 52 imposes. Therefore, the role of the pharmacist in the dispensation of these drugs is fundamental, alerting the risks that this class can cause to the consumer's health.